2008
DOI: 10.1145/1352782.1352785
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Roles of Knowledge and Cognitive Abilities in Older Adult Information Seeking on the Web

Abstract: This study investigated the influences of knowledge, particularly Internet, Web browser, and search engine knowledge, as well as cognitive abilities on older adult information seeking on the Internet. The emphasis on aspects of cognition was informed by a modeling framework of search engine information-seeking behavior. Participants from two older age groups were recruited: twenty people in a younger-old group (ages 60-70) and twenty people in an older-old group (ages 71-85). Ten younger adults (ages 18-39) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 29 publications
2
109
0
1
Order By: Relevance
“…For younger adults, in addition to the consistent main effect of task (F(1,21)=16.41, p<0.001), we also found a main effect of interface and a significant interaction effect of task and interface (F(1,21)=27.36, F (1,21)=6.34, all p's<0.05). For older adults, there was only a main effect of task with more within-category links clicked when the tasks matched with the interface.…”
Section: Interaction Of Age and Interface On Search Processsupporting
confidence: 63%
“…For younger adults, in addition to the consistent main effect of task (F(1,21)=16.41, p<0.001), we also found a main effect of interface and a significant interaction effect of task and interface (F(1,21)=27.36, F (1,21)=6.34, all p's<0.05). For older adults, there was only a main effect of task with more within-category links clicked when the tasks matched with the interface.…”
Section: Interaction Of Age and Interface On Search Processsupporting
confidence: 63%
“…For health consumers, a fundamental poverty in the mental representation of the medical domain underlies issues with terminology, and it is likely to affect three stages of information retrieval outlined by Keselman and her colleagues [43]: (i) the formation of a theory or hypothesis based on background knowledge, (ii) generation of a search goal, and (iii) evaluation of search results. Domain knowledge influences search strategies and the ability to benefit from help tools [44][45][46][47]. Therefore, the success of efforts aimed at CHV is likely to be limited without mechanisms for helping the consumer form a richer mental representation of the medical or health issue for which they seek information.…”
Section: Obstacles For Chv and Nlpmentioning
confidence: 99%
“…one that makes less demand on spatial abilities, and greater demand on vocabulary). Sharit et al (2008) showed that a combination of both Internet-related knowledge and cognitive abilities such as reasoning, working memory and perceptual speed, and to some extent verbal fluency, predicted the age-related differences in information searching performance.…”
mentioning
confidence: 99%